Perceptions of change in the environment caused by the COVID-19 pandemic: Implications for environmental policy - Hidalgo Triana, Noelia; Picornell, Antonio; Reyes-Corredera, Sergio Jesús; Circella, G.; Ribeiro, H.; Bates, A. E.; Rojo, J.; Pearman, P. B.; Artes Vivancos, J. M.; Nautiyal, S.; Brearley, F. Q.; Pereña, J.; et al. (Elsevier, 2023)
COVID-19 lockdown measures have impacted the environment with both positive and negative effects. However, how human populations have perceived such changes in the natural environment and how they may have changed their daily habits have not been yet thoroughly evaluated. The objectives of this work were to investigate (1) the social perception of the environmental changes produced by the COVID-19 pandemic lockdown and the derived change in habits in relation to i) waste management, energy saving, and sustainable consumption, ii) mobility, iii) social inequalities, iv) generation of noise, v) utilization of natural spaces, and, vi) human population perception towards the future, and (2) the associations of these potential new habits with various socio-demographic variables.
Keywords: COVID-19; Medio ambiente; Pandemic; Emerging environmental impacts; Perception; Social behaviours; Natural environment